2014
DOI: 10.4236/ajps.2014.57104
|View full text |Cite
|
Sign up to set email alerts
|

Flaming Dormant Alfalfa for Pest Control

Abstract: Alfalfa (Medicago sativa Leyss) is an important forage crop whose production is hampered by pests, including the alfalfa weevil (Hypera postica Gyllenhal) which is a major problem in many areas. Flaming during dormancy could be an alternative control measure. Late fall and early spring flaming at three intensities were compared with pesticide and no treatment for their effects on alfalfa weevil damage and weed density. In four site-years, flaming at high intensity generally reduced weevil damage to alfalfa. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Similar results were obtained byPellissier et al (2017) andHarrington et al (2021) on alfalfa and the other crops. Numerous studies have reported that if plants have an insect pest problem, pesticide usage increased plant yield and yield parameters(Sun et al, 2014;Moyer et al, 2014). In the South Kazakhstan, in rainfed areas under conventional tillage, the biggest problem is with open fallow when multiple tillage operations are conducted to control weeds, causing substantial soil erosion and degradation.…”
mentioning
confidence: 99%
“…Similar results were obtained byPellissier et al (2017) andHarrington et al (2021) on alfalfa and the other crops. Numerous studies have reported that if plants have an insect pest problem, pesticide usage increased plant yield and yield parameters(Sun et al, 2014;Moyer et al, 2014). In the South Kazakhstan, in rainfed areas under conventional tillage, the biggest problem is with open fallow when multiple tillage operations are conducted to control weeds, causing substantial soil erosion and degradation.…”
mentioning
confidence: 99%